Toll-Like Receptor 4 in Paraventricular Nucleus Mediates Visceral Hypersensitivity Induced by Maternal Separation - Hui-Li Tang; Hui-Li Tang; Gongliang Zhang; Ning-Ning Ji; Lei Du; Bin-Bin Chen; Rong Hua; Yong-Mei Zhang (Frontiers Media S.A., 2017)
Neonatal maternal separation (MS) is a major early life stress that increases the risk of emotional disorders, visceral pain perception and other brain dysfunction. Elevation of toll-like receptor 4 (TLR4) signaling in the paraventricular nucleus (PVN) precipitates early life colorectal distension (CRD)-induced visceral hypersensitivity and pain in adulthood. The present study aimed to investigate the role of TLR4 signaling in the pathogenesis of postnatal MS-induced visceral hypersensitivity and pain during adulthood. The TLR4 gene was selectively knocked out in C57BL/10ScSn mice (Tlr4-/-). MS was developed by housing the offspring alone for 6 h daily from postnatal day 2 to day 15. Visceral hypersensitivity and pain were assessed in adulthood. Tlr4+/+, but not Tlr4-/-, mice that had experienced neonatal MS showed chronic visceral hypersensitivity and pain. TLR4 immunoreactivity was observed predominately in microglia in the PVN, and MS was associated with an increase in the expression of protein and/or mRNA levels of TLR4, corticotropin-releasing factor (CRF), CRF receptor 1 (CRFR1), tumor necrosis factor-α, and interleukin-1β in Tlr4+/+ mice. These alterations were not observed in Tlr4-/- mice. Local administration of lipopolysaccharide, a TLR4 agonist, into the lateral cerebral ventricle elicited visceral hypersensitivity and TLR4 mRNA expression in the PVN, which could be prevented by NBI-35965, an antagonist to CRFR1. The present results indicate that neonatal MS induces a sensitization and upregulation of microglial TLR4 signaling activity, which facilitates the neighboring CRF neuronal activity and, eventually, precipitates visceral hypersensitivity in adulthood.Highlights(1)Neonatal MS does not induce chronic visceral hypersensitivity and pain in Tlr4-/- mice.(2)Neonatal MS increases the expression of TLR4 mRNA, CRF protein and mRNA, CRFR1 protein, TNF-α protein, and IL-1β protein in Tlr4+/+ mice.(3)TLR4 agonist LPS (i.c.v.) elicits visceral hypersensitivity and TLR4 mRNA expression in the PVN.